Learning to type with Bernie - Hoggatt, Jack P.
This book uses Microsoft Word 97 to teach word processing concepts in a series of simple lessons that avoid high-tech computer lingo. Keyboarding the entire alphabet is taught in the first eight lessons. Other word processing concepts covered include insert and delete tables, columns, and graphics. Although designed using Word 97, it can be easily adapted for use with Word 6 and Word 7. The CD-ROM contains data files that reduce typing time